Comoros : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this study, the following statistical data are presented in detail: GDP at current market prices; prices of export crops; production and consumption of electricity; indicators of tourism activity; indicators of population, education, and employment; monetary survey; summary statement of the central bank; structure of interest rates; balance of payments; volume and value of principal exports and imports; breakdown of the government wage bill; external debt outstanding by creditors; summary of tax system; consolidated government expenditure; wage bill developments by ministry; and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet